Kurikulum Pendidikan Islam Terpadu: Studi Atas Implementasi Kurikulum Sains dan Agama pada SDIT Insan Cendikia Lamongan - Nur Hakim; Nur Azizah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the implementation of the integrated science and religion curriculum at SDIT Insan Cendikia Lamongan and to identify the challenges and opportunities faced, driven by the imbalance in student achievement, with students tending to perform better in science than in religion. Unlike previous studies, this research specifically and thoroughly explores the context of curriculum integration at the SDIT level in Lamongan. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation, then analyzed through data reduction, presentation, and drawing of conclusions. Key findings indicate that curriculum implementation is well-planned and structured, resulting in students who excel academically while possessing strong moral character. However, challenges such as maintaining curriculum balance, resource limitations, and resistance to the curriculum were also identified. This research offers a new perspective on science-religion integration in fostering students’ critical thinking and moral foundations.